Abnormal behaviour in a tricolour male cat - Simon, A. J.; Dhaliwal, Gurmeet Kaur; Abd Rasid, Omar; Yusoff, Rosnina (2005)
A 1-year-old tricolour intact male cat was presented to the University Veterinary Hospital of the University Putra Malaysia with a primary complaint of attempting to mount neutered cats within the same household. Serum concentration of testosterone was within normal range. Detailed history, physical examination and testicular histology suggest that this behaviour was a result of a combination of factors, namely the Klinefelter syndrome, sexual maturity and shifts in social hierarchy.